Coating composition and coating material having antibacterial, antiviral and antifouling properties
A coating composition with specific polymers and antibacterial agents ensures durable antibacterial and antiviral properties by using a combination of polyorganosiloxane and inorganic fine particles, maintaining effectiveness through wiping and alcohol exposure.
Patent Information
- Application Number
- JP2021022743
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-11
- Filing Date
- 2021-02-16
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-02-16
AI Technical Summary
Existing antibacterial and antiviral coatings lose effectiveness upon repeated wiping or exposure to alcohol, leading to a decrease in surface antibacterial and antiviral properties.
A coating composition comprising a polymer with a polyorganosiloxane structure and hydroxyl groups, a polymer without polyorganosiloxane structure, a curing agent with functional groups, and an antibacterial/antiviral agent, including inorganic fine particles and a dispersant, which maintains antibacterial and antiviral properties even after wiping or alcohol exposure.
The coating composition provides durable antibacterial and antiviral properties, maintaining effectiveness even after wiping and alcohol exposure, with improved film strength and appearance.
Smart Images

Figure 0007619075000001 
Figure 0007619075000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating composition having antibacterial, antiviral and antifouling properties, and to a coating material for plastic films and paper using the same. [Background technology]
[0002] With the recent rise in awareness of hygiene, antibacterial agents, antiviral agents, antifungal agents, disinfectants, etc. are used to prevent the spread and infection of bacteria, mold, and other fungi in food and pharmaceutical factories, buildings such as hospitals and nursing homes, food and kitchen utensils, medical instruments, medical equipment, and even general household products. Therefore, it is desired to impart antibacterial and antiviral properties to various components not only in public facilities but also in general homes.
[0003] To solve these problems, organic or inorganic antibacterial agents have been proposed. In particular, inorganic antibacterial agents have traditionally been used as silver ions (Ag + ), zinc ion (Zn 2+ ), and divalent copper ions (Cu 2+ It is known that metal ions such as ammonium nitrate, ammonium nitrate, and the like inhibit the proliferation of microorganisms or have a bactericidal effect on microorganisms (for example, Patent Document 1). Based on this knowledge, a large number of antimicrobial materials have been developed, including those in which these metal ions are supported on substances such as zeolite or silica gel, and those in which the above-mentioned metals are combined with titanium oxide having a photocatalytic effect, and antibacterial coating agents using these materials have also been developed. However, in some cases, when the surface of a coated product is repeatedly wiped, the effect does not last as long as it should. Also, during actual printing, the active ingredients settle out, reducing the proportion of the antibacterial and antiviral ingredients on the surface of the coating composition, and there are cases where effective antibacterial and antiviral properties are not obtained. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-221304 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a coating composition which has a printed layer in good condition, good antibacterial and / or antiviral properties, and good alcohol resistance, and which can maintain the antibacterial and / or antiviral properties even after wiping. [Means for solving the problem]
[0006] As a result of intensive research and repeated experiments in order to achieve the above object, the inventors have found that the object of the present application can be achieved by using the coating composition described below, and have completed the present invention based on this finding.
[0007] That is, the present invention relates to a coating composition comprising: (a) a polymer having a polyorganosiloxane structure and a hydroxyl group; (b) a polymer not having a polyorganosiloxane structure; (c) a curing agent having a functional group capable of reacting with the hydroxyl group; (d) an antibacterial and antiviral agent; and (e) a dispersant.
[0008] The present invention also relates to the above coating composition, wherein the antibacterial and antiviral agent (d) comprises at least one selected from the group consisting of inorganic fine particles (d-1) containing at least one metal ion selected from the group consisting of gold, silver, copper, tin, zinc, and platinum, calcium oxide (d-2), a component extracted from Kumazasa (d-3), and a compound having a cationic group in the molecule (d-4).
[0009] The present invention also relates to the above coating composition, wherein the content of the antibacterial and antiviral agent (d) is 0.15 to 15 mass% relative to 100 mass% of the total solid content of the polymer (a), the polymer (b), and the curing agent (c).
[0010] The present invention also relates to the above coating composition, wherein the antibacterial and antiviral agent (d) is in particulate form and has an average particle size of 0.1 μm to 5.0 μm.
[0011] The present invention also relates to the above coating composition, wherein the dispersant (e) has a carboxyl group and / or an amino group.
[0012] The present invention also relates to a coated article having a coating layer formed from the above coating composition on a plastic film or a paper substrate. Effect of the Invention
[0013] The present invention makes it possible to provide a coating composition which has a good printed layer condition, good antibacterial and / or antiviral properties, good alcohol resistance, and which can maintain the antibacterial and / or antiviral properties even after wiping. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention will be described. The following description of the constituent elements is an example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the spirit of the invention.
[0015] In the following description, the coating composition containing the antibacterial and / or antiviral agent (d) may be simply referred to as the "composition", but this has the same meaning. The layer formed by printing or the like from the coating composition containing the antibacterial and / or antiviral agent is called the "coat layer", but this has the same meaning. Note that "antibacterial and / or antiviral properties" means having antibacterial and / or antiviral properties, and it is preferable that the coating composition has antibacterial and / or antiviral properties.
[0016] Below, we will explain in detail each component that constitutes the coating composition containing the antibacterial and antiviral agent. Note that "polymer" and "resin" are treated as synonyms. In the following explanation, "(meth)acrylic" refers to both "methacrylic" and "acrylic". The same applies to (meth)acrylate.
[0017] (Coating composition) The coating composition of the present invention includes a polymer (a) having a polyorganosiloxane structure and a hydroxyl group, a polymer (b) not having a polyorganosiloxane structure, a curing agent (c) having a functional group capable of reacting with the hydroxyl group, an antibacterial / antiviral agent (d) and a dispersant (e). The total mass of the coating composition contains preferably 20 to 80 mass% of the polymer (a) and the polymer (b), more preferably 30 to 70 mass%. The solid content of the coating composition is preferably 15 to 40 mass%, more preferably 20 to 35 mass%. The "solid content" refers to the total mass% of nonvolatile content. The polymer (a) and the polymer (b) are preferably contained in a mass ratio of 1:99 to 99:1, and more preferably 2:98 to 50:50.
[0018] (Polymer (a) Having a Polyorganosiloxane Structure and a Hydroxyl Group) The polymer (a) having a polyorganosiloxane structure and a hydroxyl group used in the present invention imparts antifouling properties, and also enhances antibacterial and antiviral properties by synergistic effects when used in combination with the polymer (b) not having a polyorganosiloxane structure and the antibacterial and antiviral agent (d) described below. The polymer (a) may be, for example, an acrylic resin, a polyester resin, a polyurethane resin (e.g., polyester urethane resin, polyether urethane resin, etc.), an epoxy resin, etc., as long as it has a polyorganosiloxane structure and a hydroxyl group in its structure, but is not limited thereto, and is preferably an acrylic resin having a polyorganosiloxane structure and a hydroxyl group. The polymer (a) is preferably a block polymer, a graft polymer, etc.
[0019] The acrylic resin having the polyorganosiloxane structure and the hydroxyl group is preferably a polymer (a) obtained by copolymerizing a (meth)acrylic monomer having a polyorganosiloxane structure with another monomer (including a (meth)acrylic monomer) using a polymerization initiator, for example, as an embodiment. As the "(meth)acrylic monomer having a polyorganosiloxane structure", for example, polyorganosiloxane compounds containing a vinyl group at one end, such as TSL9705 manufactured by Toshiba Silicone Co., Ltd., polyorganosiloxane compounds containing a (meth)acryloxy group at one end, such as Silaplane FM-0711, FM-0721, FM-0725 manufactured by JNC Corporation, etc. can be suitably mentioned. In addition, when the (meth)acrylic monomer having a polyorganosiloxane structure does not have a hydroxyl group, it is preferable that the "other monomer" contains a (meth)acrylic monomer having a hydroxyl group, and examples of the "other monomer" include, but are not limited to, 2-hydroxyethyl (meth)acrylate, 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polytetramethylene glycol mono(meth)acrylate, and hydroxystyrene. The "other monomer" may contain a monomer that does not have a hydroxyl group.
[0020] As the monomer not having a hydroxyl group, a (meth)acrylic monomer (aliphatic (meth)acrylic monomer, aromatic (meth)acrylic monomer) and a styrene-based monomer can be suitably used. The (meth)acrylic monomer can be, for example, an alkyl (meth)acrylate. The alkyl (meth)acrylate can be, for example, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, and lauryl (meth)acrylate, and further, other than the hydroxyl group, it may contain a carboxyl group, an amino group, an epoxy group, an N-alkoxyalkyl group, and the like.
[0021] The polymer can be produced by a known method, for example, solution polymerization, etc., using these solvents. Examples of the solvents that can be used include alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol methyl ether, and diethylene glycol methyl ether; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ethers such as tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, and diethylene glycol dimethyl ether; hydrocarbons such as hexane, heptane, and octane; aromatics such as benzene, toluene, xylene, and cumene; and esters such as ethyl acetate and butyl acetate. The solvent may be a mixture of two or more kinds. The concentration of the monomers charged during synthesis is preferably 10 to 80% by weight.
[0022] As the polymerization initiator, a typical peroxide or azo compound, such as benzoyl peroxide, azoisobutylvalenonitrile, azobisisobutyronitrile, di-t-butyl peroxide, t-butyl perbenzoate, t-butyl peroctoate, or cumene hydroxyperoxide, is used, and the polymerization temperature is 50 to 140°C, preferably 70 to 140°C.
[0023] (Polymer (b) not having a polyorganosiloxane structure) The polymer (b) not having a polyorganosiloxane structure can be, like the polymer (a), a polymer such as an acrylic resin, a polyester resin, a polyurethane resin (e.g., a polyester urethane resin, a polyether urethane resin, etc.), or an epoxy resin, and does not have a polyorganosiloxane structure. Among them, an acrylic resin is preferable. In this case, a (meth)acrylic monomer, a styrene-based monomer, etc. not having a polyorganosiloxane structure can be polymerized using the same materials and methods as the polymer (a).
[0024] The weight average molecular weight of the polymer (a) having a polyorganosiloxane structure and a hydroxyl group and the polymer (b) not having a polyorganosiloxane structure is preferably 5,000 to 50,000, more preferably 10,000 to 40,000, and further preferably 15,000 to 35,000. The weight average molecular weight refers to a value measured by GPC (gel permeation chromatography). The hydroxyl value of the polymer (a) is preferably 10 to 250 mgKOH / g, more preferably 50 to 200 mgKOH / g. Within this range, the strength of the coating layer is improved, the coating layer has good resistance in a felt-tip pen wipe test and an alcohol wipe test, and blocking of the coating layer can be suppressed even when a curing agent is added.
[0025] (Antibacterial and antiviral agents (d)) The antibacterial and antiviral agent (d) is used to exhibit antibacterial and antiviral properties. Examples of the antibacterial and antiviral agent (d) include inorganic and organic antibacterial and antiviral agents. Inorganic agents include inorganic fine particles (d-1) and inorganic oxides, and organic agents include the compounds described below. The antibacterial and antiviral agent (d) shows a synergistic effect when used in combination with the polymer (a) having a polyorganosiloxane structure and the polymer (b) not having a polyorganosiloxane structure, and is effective in antibacterial, antiviral, and antifouling properties. The antibacterial and antiviral agent (d) preferably contains at least one of inorganic fine particles (d-1) containing at least one metal ion selected from the group consisting of gold, silver, copper, tin, zinc and platinum, calcium oxide (d-2), a component extracted from Japanese kumazasa (d-3), and a compound having a cationic group in the molecule (d-4).
[0026] (Inorganic fine particles (d-1) containing at least one metal ion selected from the group consisting of gold, silver, copper, tin, zinc and platinum) Suitable examples of inorganic fine particles (d-1) include inorganic fine particles (also called antibacterial solid particles) in which at least one type of metal ion such as gold, silver, copper, tin, zinc, platinum, etc. is supported on zeolite, hydroxyapatite, or calcium phosphate, and metal complexes having the above metal ions as central metals, and inorganic oxides. The antibacterial solid particles are zeolite, hydroxyapatite, or calcium phosphate in which antibacterial metal ions such as gold, silver, copper, zinc, platinum, etc. are incorporated. Zeolite is a type of crystalline aluminosilicate, which is composed of aluminum, silicon, and an alkali metal, and has a crystalline structure with voids. Specific products include Novalon (Toagosei Co., Ltd.), Zeomic (manufactured by Sinanen Zeomic Co., Ltd.), Apagen SP-200 (manufactured by Zanki Co., Ltd.), Apagen SP-1 (manufactured by Zanki Co., Ltd.), Apacider AK (manufactured by Zanki Co., Ltd.), Apacider AW (manufactured by Zanki Co., Ltd.), Apacider Z (manufactured by Zanki Co., Ltd.), Biocide (Taisho Technos), PBM-OJ (manufactured by Pacific Beam Mold), PBM-OJ Plus (manufactured by Pacific Beam Mold), CS-100 (manufactured by Sumitomo Osaka Cement Co., Ltd.), Tribolite (manufactured by Kanae Paint Co., Ltd.), and Rasap (manufactured by Rasa Kogyo Co., Ltd.). It is preferable that the metal ion contains silver, particularly in consideration of its effects on the human body.
[0027] The antibacterial and antiviral agent (d) preferably contains an inorganic oxide, preferably calcium oxide (d-2) or zinc oxide. Other inorganic oxides include aluminum oxide (alumina), silicon oxide (silica), zirconium silicate, rutile-type titanium oxide, tin oxide, zirconium oxide, cerium oxide, magnesium fluoride, iron oxide, copper oxide, antimony oxide, cryolite, fluorite, apatite, calcite, gypsum, and talc.
[0028] Organic antibacterial and antiviral agents include halogen-based, phenol-based, imidazole-based, thiazole-based, guanidine-based, pyridine-based, organic arsenic-based, Kumazasa extract (d-3), compounds with cationic groups in the molecule (d-4), amide-based, and amino-based metal surfactants. Specifically, they are described in "Microorganism Sterilization, Disinfection, and Antifungal Technology" (Society of Hygienic Technology), "Antibacterial and Antifungal Handbook" (Japan Society of Antibacterial and Antifungal Agents), and "Dictionary of Antibacterial and Antifungal Agents" (Japan Society of Antibacterial and Antifungal Agents). Among these, it is preferable to contain a component extracted from Kumazasa (d-3) and a compound having a cationic group in the molecule (d-4). The compound (d-4) having a cationic group in the molecule is, for example, a compound having a cationic group such as a quaternary ammonium salt or a sulfonium salt in the molecule, and preferably a compound having a quaternary ammonium salt. The compound (d-4) having a cationic group in the molecule may be a low molecular weight compound or a high molecular weight compound. The preferred embodiments of the compound (d-4) having a cationic group in the molecule are as follows: low molecular weight compounds, such as benzalkonium chloride and benzathonium chloride, are suitable. High molecular weight compounds, such as acrylic resins containing acrylic monomers containing quaternary ammonium salts, are suitable. High molecular weight compounds are preferably polymers.
[0029] The antibacterial and antiviral agent (d) may be either solid particles or liquid, but is more preferably present in the coating layer as solid particles. By being present in a solid state, the antibacterial and antiviral performance is more likely to be sustained since the agent does not leave the coating layer after rubbing the coating layer. The average particle size is preferably 0.05 to 10 μm, more preferably 0.05 to 7 μm, and even more preferably 0.1 to 5 μm. This is because the antiviral function is more likely to be exhibited by making the average particle size larger than the coating layer thickness. The content of the antibacterial and antiviral agent is preferably 0.1 to 20 mass% based on 100 mass% of all solids except the antibacterial and antiviral agent, more preferably 0.15 to 15 mass%, and even more preferably 0.3 to 12 mass%, in order to improve the film strength and appearance of the coating layer. The average particle size refers to the D50 measured value by a laser diffraction / scattering method, and can be measured using, for example, a particle size distribution measuring device manufactured by Microtrac-Bell, such as the Microtrac MT3000II series.
[0030] (Curing agent (c) having a functional group capable of reacting with a hydroxyl group) The curing agent (c) having a functional group capable of reacting with a hydroxyl group is not particularly limited as long as it has a functional group capable of reacting with a hydroxyl group. The curing agent (c) not only increases the film strength of the coating layer, but is also expected to be effective in terms of antibacterial and antiviral properties. The following are preferred embodiments of the curing agent (c). The curing agent (c) is preferably contained in an amount of 5 to 50 mass % and more preferably 10 to 35 mass % of the total mass of solids in the coating composition.
[0031] The curing agent (c) is preferably an isocyanate-based curing agent. As the isocyanate-based curing agent, diisocyanate, diisocyanate adduct-based curing agent, isocyanurate-based curing agent, etc. are preferable. Specifically, diisocyanates such as tolylene diisocyanate, naphthylene-1,5-diisocyanate, o-toluylene diisocyanate, diphenylmethane diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, m-xylene diisocyanate, p-xylene diisocyanate, lysine diisocyanate, hydrogenated 4,4'-diphenylmethane diisocyanate, hydrogenated tolylene diisocyanate, etc. may be mentioned. Preferred are adducts of diisocyanates and polyhydric alcohols or polyamines (diisocyanate adduct-based curing agents), and polyvalent isocyanates such as triphenylmethane triisocyanate, polymethylene polyphenyl isocyanate, and coronate L. Also preferred are isocyanurate compounds, which are trimers of diisocyanates, and derivatives thereof (isocyanurate-based curing agents).
[0032] As the curing agent (c) having a functional group capable of reacting with a hydroxyl group, the following curing agents can be suitably used in addition to the above-mentioned isocyanate-based curing agents.
[0033] For example, melamine compounds having an alkylol group or an alkoxy group, such as hexamethylol melamine, hexamethoxymethyl melamine, and hexabutoxymethyl melamine; Amino resins such as cyanuric acid, ammelide, melamine, benzoguanamine, diethanolamine, triethanolamine, diaminopyridine, benzoguanamine resin, methanol-modified melamine resin, and urea resin; Hydrazine, adipic dihydrazide (ADH) and other hydrazine compounds, Linear diamines such as ethylenediamine, propanediamine, butanediamine, pentanediamine, hexanediamine, diaminooctane, diaminodecane, diaminododecane, 2,5-dimethyl-2,5-hexamethylenediamine, polyoxypropylenediamine, diethylenetriamine, triethylenetetramine, and tetraethylenepentamine; cyclic diamines such as menthene diamine, isophorone diamine, bis(4-amino-3-methyldicyclohexyl)methane, diaminodicyclohexylmethane, 3,9-bis(3-aminopropyl)-2,4,8,10-tetraoxaspiro[5.5]undecane, 1,4-bis(2-amino-2-methylpropyl)piperazine, m-xylenediamine, polycyclohexylpolyamines, bis(aminomethyl)bicyclo[2.2.1]heptane, and methylenebis(furanmethanamine); Polyamines such as 1,6-hexamethylenediamine, triethylenetetramine, tetraethylenepentamine, and diethylenetriamine, The above are preferred examples.
[0034] Also, dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, hexanedioic acid, citric acid, maleic acid, methylnadic acid, dodecenylsuccinic acid, sebacic acid, pyromellitic acid, hexahydrophthalic acid, and tetrahydrophthalic acid, and their acid anhydrides, dialdehydes such as glyoxal and terephthalaldehyde; amino acids such as glycine and alanine and their lactams; hydroxycarboxylic acids such as citric acid, 12-hydroxystearic acid, and 6-hydroxypentanoic acid and their lactones; Bis-epoxy compounds such as ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and phthalic acid diglycidyl ester, manufactured by Yuka Shell Epoxy Co., Ltd., product names are Epicoat 801, 802, 807, 815, 827, 828, 834, 815X, 815XA1, 828EL, 828XA, 1001, 1002, 1003, 1 Examples of the epoxy resins include 055, 1004, 1004AF, 1007, 1009, 1010, 1003F, 1004F, 1005F, 1100L, 834X90, 1001B80, 1001X70, 1001X75, 1001T75, 5045B80, 5046B80, 5048B70, 5049B70, 5050T60, 5050, 5051, 152, 154, 180S65, 180H65, 1031S, 1032H60, 604, and 157S70; phosphorus compounds such as pyrophosphoric acid, ethyl phosphite, bisphenol A-modified polyphosphoric acid, and triphenyl phosphite; and phosphoric acid dichloride compounds.
[0035] (Dispersant (e)) The dispersant (e) is used to stably disperse the antibacterial and antiviral agent and make it uniformly present on the surface of the coating layer. If the antibacterial and antiviral agent is uniformly dispersed on the surface of the coating layer, it is possible to maintain the antibacterial and antiviral properties even after wiping. As the dispersant (e), a surfactant having anionic, nonionic, cationic, or amphoteric properties, or a resin-type dispersant having an anionic group such as a carboxyl group or a cationic group such as an amino group in the skeleton can be suitably used. Furthermore, a dispersant having a carboxyl group and / or an amino group is preferable. Specific examples include ANTI-TERRA-U (manufactured by Big Chemie Co., Ltd.), Disper BYK9076, 9077, 102, and 109 (manufactured by Big Chemie Co., Ltd.), etc. The amount of the antibacterial and antiviral agent to be added is not particularly limited, but from the viewpoint of storage stability, it is preferably contained in the composition at 0.1 to 10 mass% based on the total mass of the antibacterial and antiviral agent, and more preferably 0.1 to 6 mass% or 0.1 to 3 mass%.
[0036] (Organic solvent) The coating composition of the present invention preferably contains an organic solvent used during printing, and examples of the organic solvent include alcohol-based solvents such as methanol, ethanol, and isopropanol, ester-based solvents such as ethyl acetate and propyl acetate, glycol ether-based solvents such as propylene glycol monomethyl ether, ketone-based solvents such as acetone and methyl ethyl ketone, aromatic solvents such as toluene and xylene, and mixtures thereof. When an isocyanate-based curing agent is used, it is preferable not to use an alcohol-based solvent.
[0037] (Other additives) The composition of the present invention may also contain, as necessary, known and used ultraviolet absorbers, light stabilizers, antifungal agents, antistatic agents, antioxidants, colorants, lubricants, fillers, latent curing agents, flame retardants, plasticizers, and the like.
[0038] (Plastic film or paper) The plastic film or paper used in the present invention is a substrate for printing and coating, and any known and used plastic film or paper can be used without any particular limitation. In addition, the antibacterial and antiviral agent may not be printed directly onto the substrate, and a primer layer, anchor layer, or printed pattern layer may be interposed between the plastic film or paper and the coating layer. Examples of plastic films include polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate, polycarbonate, and polylactic acid, polystyrene-based resins such as polystyrene, AS resin, and ABS resin, nylon, polyamide, polyvinyl chloride, polyvinylidene chloride, cellophane, aluminum, and the like, or film-like substrates made of composite materials thereof. Vapor-deposited substrates in which inorganic compounds such as silica, alumina, and aluminum are vapor-deposited on polyethylene terephthalate and nylon films can also be used, and the vapor-deposited surface may be coated with polyvinyl alcohol or the like. Papers used as substrates are not particularly limited, and include tissue paper, craft paper, titanium paper, coated cardboard, art paper, polyethylene-coated paper, and matte-coated paper, among which coated cardboard, art paper, and polyethylene-coated paper are preferred because of their difficulty in permeating.
[0039] (Coating method) In order to uniformly coat the coating composition of the present invention and obtain a coating product with good appearance, it is preferable to use a wet coating method. As the wet coating method, a gravure coating method, a die coating method, etc. can be used. The gravure coating method may be a so-called printing method, in which a gravure roll with a concave and convex engraved surface is immersed in a coating liquid, the coating liquid attached to the concave and convex portions of the gravure roll surface is scraped off with a doctor blade, and the liquid is stored in the concave portions, so that it is accurately measured and transferred to a substrate. The gravure coating method can coat a low-viscosity liquid thinly. The die coating method is a method in which the liquid is pressurized and extruded from a coating head called a die to coat the substrate. The die coating method enables high-precision coating. Furthermore, since the liquid is not exposed to the outside air during coating, the concentration of the coating liquid is less likely to change due to drying. Other wet coating methods include a spin coating method, a bar coating method, a reverse coating method, a roll coating method, a slit coating method, a dipping method, a spray coating method, a kiss coating method, a reverse kiss coating method, an air knife coating method, a curtain coating method, and a rod coating method. An appropriate method can be selected from these methods depending on the required film thickness. In addition, when productivity is taken into consideration, the wet coating method allows lamination at a line speed of several tens of meters per minute (for example, about 20 m / min), which allows mass production and improves production efficiency.
[0040] A method for drying the coating composition will now be described. When using thermal energy, drying can be performed in an environment of room temperature to about 200°C, but when using a plastic film, a temperature of 50 to 120°C is preferred in consideration of the heat resistance of the plastic. When the curing agent (c) also contains an isocyanate-based curing agent, it is preferred to leave the composition to stand (age) for 1 to 7 days at room temperature to 40°C. EXAMPLES
[0041] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the examples and comparative examples, "parts" and "%" respectively mean "parts by mass" and "% by mass" unless otherwise specified.
[0042] (Acid value, hydroxyl value) The measurement was performed according to the method described in JIS K0070. (amine value) The amine value was calculated by the following method in accordance with JIS K0070, in terms of the equivalent amount of hydrochloric acid and the equivalent amount of potassium hydroxide required to neutralize the amino groups contained in 1 g of resin. 0.5 to 2 g of sample was precisely weighed out (sample solid content: Sg). 50 mL of a mixed solution of methanol / methyl ethyl ketone = 60 / 40 (mass ratio) was added to the precisely weighed sample to dissolve it. Bromophenol blue was added to the obtained solution as an indicator, and the obtained solution was titrated with 0.2 mol / L ethanolic hydrochloric acid solution (titer: f). The point at which the color of the solution changed from green to yellow was set as the endpoint, and the titration amount (A mL) at this point was used to calculate the amine value according to the following (Equation 2). (Equation 2) Amine value = (A x f x 0.2 x 56.108) / S [mgKOH / g]
[0043] (Weight average molecular weight) The weight average molecular weight was determined as a polystyrene-equivalent molecular weight by measuring the molecular weight distribution using a GPC (gel permeation chromatography) device (Shodex GPC System-21, manufactured by Showa Denko KK). The measurement conditions are as follows. Column: The following multiple columns are connected in series. Tosoh Corporation, TSKgel SuperAW2500, Tosoh Corporation, TSKgel SuperAW3000, Tosoh Corporation, TSKgel SuperAW4000, TSKgel Guardcolumn SuperAWH, manufactured by Tosoh Corporation Detector: RI (differential refractometer), Measurement conditions: column temperature 40°C, Eluent: Tetrahydrofuran Flow rate: 1.0mL / min
[0044] (glass transition temperature) The glass transition temperature (Tg) was determined by DSC (differential scanning calorimetry). The measurement was performed using a Rigaku Corporation DSC8231 instrument, with a measurement temperature range of -70 to 250°C, a heating rate of 10°C / min, and the midpoint between the endothermic start and end temperatures due to the glass transition in the DSC curve was taken as the glass transition temperature.
[0045] (Production Example 1) Production of a polymer (a-1) having a polyorganosiloxane structure and a hydroxyl group. 50 parts of Silaplane FM-0711 (polysiloxane compound containing methacryloxy groups at one end) manufactured by JNC Corporation, 36 parts of 2-hydroxyethyl methacrylate, 14 parts of methyl methacrylate, and 200 parts of methyl ethyl ketone (MEK) were charged into a four-neck flask equipped with a cooling tube, a stirrer, and a thermometer, and the mixture was heated to 80°C while stirring under a nitrogen stream, and 1.6 parts of azobisisobutyronitrile were added and polymerized for 2 hours. 0.4 parts of azobisisobutyronitrile was added and polymerized for 2 hours to obtain a polymer (a-1) solution having a polyorganosiloxane structure and a weight average molecular weight of about 19,000 and a hydroxyl value of 51 (mgKOH / g).
[0046] (Production Example 2) Production of a polymer (a-2) having a polyorganosiloxane structure and a hydroxyl group. JNC Corporation's Silaplane FM-0711 (polysiloxane compound containing methacryloxy groups at one end) 10 parts, 4-hydroxybutyl methacrylate 25 parts, methyl methacrylate 40 parts, butyl methacrylate 14 parts, butyl acrylate 10 parts, acrylic acid 1 part, methyl ethyl ketone (MEK) 200 parts were charged into a four-neck flask equipped with a cooling tube, a stirrer, and a thermometer, and the mixture was heated to 80 ° C. while stirring under a nitrogen stream, and 1.6 parts of azobisisobutyronitrile were added and polymerized for 2 hours. Further, 0.4 parts of azobisisobutyronitrile was added and polymerized for 2 hours to obtain a polymer (a-2) solution having a weight average molecular weight of about 19,500 having a polyorganosiloxane structure, an acid value of 2.6 (mgKOH / g), and a hydroxyl value of 32 (mgKOH / g).
[0047] (Production Example 3) Production of a polymer (a-3) having a polyorganosiloxane structure and a hydroxyl group. JNC Corporation's Silaplane FM-0711 (polysiloxane compound containing methacryloxy groups at one end) 45 parts, 4-hydroxybutyl methacrylate 31 parts, butyl methacrylate 20.5 parts, butyl acrylate 1.0 parts, acrylic acid 2.5 parts, methyl ethyl ketone (MEK) 200 parts were charged into a four-neck flask equipped with a cooling tube, a stirrer, and a thermometer, and the mixture was heated to 80 ° C. while stirring under a nitrogen stream, and 1.6 parts of azobisisobutyronitrile were added and the polymerization reaction was carried out for 2 hours. Further, 0.4 parts of azobisisobutyronitrile was added and the polymerization was carried out for 2 hours, and a polymer (a-3) solution having a weight average molecular weight of about 19,100 having a polyorganosiloxane structure, an acid value of 6.5 (mgKOH / g), and a hydroxyl value of 40 (mgKOH / g) was obtained.
[0048] (Production Example 4) Production of polymer (aa) having a polyorganosiloxane structure and no hydroxyl group. 50 parts of Silaplane FM-0711 (polysiloxane compound containing methacryloxy groups at one end) manufactured by JNC Corporation, 14 parts of methyl methacrylate, 18 parts of butyl methacrylate, 18 parts of butyl acrylate, and 200 parts of methyl ethyl ketone (MEK) were charged into a four-neck flask equipped with a cooling tube, a stirrer, and a thermometer, and the mixture was heated to 80 ° C. while stirring under a nitrogen stream, and 1.6 parts of azobisisobutyronitrile was added and the polymerization reaction was carried out for 2 hours. Further, 0.4 parts of azobisisobutyronitrile was added and the polymerization was carried out for 2 hours to obtain a polymer (aa) solution having a weight average molecular weight of about 19,300 having a polyorganosiloxane structure.
[0049] (Production Example 5) Production of polymer (b-1) having no polyorganosiloxane structure. 36 parts of 2-hydroxyethyl methacrylate, 50 parts of methyl methacrylate, 14 parts of butyl methacrylate, and 200 parts of methyl ethyl ketone (MEK) were charged into a four-neck flask equipped with a cooling tube, a stirrer, and a thermometer, and the mixture was heated to 80°C while stirring under a nitrogen stream, and 1.6 parts of azobisisobutyronitrile was added and polymerized for 2 hours. 0.4 parts of azobisisobutyronitrile was added and polymerized for 2 hours to obtain a polymer (b-1) solution having a weight average molecular weight of about 17,000 and a hydroxyl value of 51 (mgKOH / g) without a polyorganosiloxane structure.
[0050] (Production Example 6) Production of polymer (b-2) having no polyorganosiloxane structure. 25 parts of 2-hydroxyethyl methacrylate, 40 parts of methyl methacrylate, 34 parts of butyl methacrylate, 1 part of acrylic acid, and 200 parts of methyl ethyl ketone (MEK) were charged into a four-neck flask equipped with a cooling tube, a stirrer, and a thermometer, and the mixture was heated to 80°C while stirring under a nitrogen stream, and 1.6 parts of azobisisobutyronitrile were added and polymerized for 2 hours. 0.4 parts of azobisisobutyronitrile was added and polymerized for 2 hours to obtain a polymer (b-1) solution having a weight average molecular weight of about 17,300 and a hydroxyl value of 36 (mgKOH / g) without a polyorganosiloxane structure.
[0051] Example 1 30 parts of polymer (a-1) solution, 30 parts of polymer (b-1) solution, 0.3 parts of dispersant (e-1), and 0.3 parts of antibacterial agent (d-1) (silver-supported zirconium particles, average particle size 2.1 μm) were mixed and stirred for 30 minutes with a disperser equipped with a stirring blade to obtain a dispersion. Furthermore, 12 parts of curing agent (c-1) (hexamethylene diisocyanate isocyanurate trifunctional (NCO% 16%)) were added at the time of printing to obtain a coating composition J1 of the present invention.
[0052] The above-mentioned coating composition J1 was diluted with methyl ethyl ketone, the viscosity was adjusted to 18 seconds using Zahn Cup No. 3 (manufactured by Rigo Co., Ltd.), and the diluted composition was printed on a polyethylene terephthalate film with a thickness of 25 μm using a gravure printing machine to obtain a coated product of Example 1. The coated product was aged in an oven at 40° C. for 3 days.
[0053] (Examples 2 to 17 and Comparative Examples 1 to 6) Coating compositions J2 to J18 and JJ1 to JJ6 were obtained in the same manner as in Example 1, except that the substances and blending ratios shown in Table 1 were used. Also, coated products were obtained in the same manner as above. The abbreviations in the table stand for the following. c-2: Trimethylolpropane adduct of tolylene diisocyanate (NCO% 13%) d-1: Silver-loaded zirconium inorganic antibacterial agent (average particle size 2.5 μm) d-1-2: Silver-zinc phosphate calcium inorganic antibacterial agent (average particle size 7.5 μm) d-2: Calcium oxide (Natural Japan, average particle size 6 μm) d-3: Kumazasa extract powder (manufactured by Toyo Adle Co., Ltd.) d-4: Benzalkonium chloride / inorganic antibacterial agent (average particle size 8.5 μm) d-4-2: Cationic polymer / inorganic material (average particle size 2.5 μm) d-5: Zinc oxide (Sakai Chemical Industry Co., Ltd., average particle size 2.0 μm) e-1: Dispersant, acid value 44mgKOH / g, amine value 38mgKOH / g (BYK) e-2: Dispersant, amine value 140mgKOH / g (BYK) e-3: Dispersant, acid value 101mgKOH / g (BYK)
[0054] (Characteristics evaluation) The coating compositions obtained in the above Examples and Comparative Examples were used to evaluate the following characteristics.
[0055] <Evaluation of the surface condition of the printed layer> The appearance of the coating was evaluated visually. A: A smooth and shiny surface. B: Slightly less glossy than A. C: The surface is rough.
[0056] <Felt-tip pen wipe test> To evaluate the stain resistance, a line was drawn using an oil-based felt pen, and the process of wiping with a dry cloth was repeated 99 times, and the ease of wiping after the 100th wipe was evaluated. A: No felt-tip pen marks were left after the wipe test. B: Even after the wipe test, faint felt-tip pen marks remained. C: Clear felt-tip pen marks remain even after the wipe test.
[0057] <Alcohol wipe test> Each coating was rubbed 10 times with a cloth soaked in a 78% aqueous solution of ethanol at a load of 500 g, and the surface condition at the end was visually evaluated. These were then used as test samples for antibacterial and antiviral tests. A: There was no change on the surface of the coating layer, and the antibacterial and antiviral properties decreased by less than 20% compared to before the test. B: There is some change on the surface of the coating layer, and the antibacterial and antiviral properties are reduced by 20% to less than 80% compared to before the test. C: The surface of the coating layer has deteriorated, and the antibacterial and antiviral properties have decreased by more than 80% compared to before the test.
[0058] <Antibacterial test> The test samples were subjected to antibacterial activity tests against Escherichia coli or Staphylococcus aureus in accordance with the Japanese Industrial Standard JIS Z 2801:2000 "Antibacterial processed products - Antibacterial test methods, antibacterial effect" 5.2 Test methods for plastic products, etc. The test results are shown in Table 2.
[0059] The "antibacterial activity value (R)" shown in Table 2 is a numerical value defined as R = Log(B / A) - Log(C / A) = Log(B / C). In this formula, A represents the average viable bacterial count in untreated test samples (not coated with antibacterial OP varnish, etc.) immediately after inoculation, B represents the average viable bacterial count in untreated test samples (not coated with antibacterial coating composition, etc.) after 24 hours, and C represents the average viable bacterial count in test samples coated with antibacterial OP varnish after 24 hours. If the antibacterial activity value (R) is 2.0 or higher, it is determined that there is an antibacterial effect.
[0060] <Antiviral test> For the test samples, influenza virus liquid was used instead of bacterial liquid according to the film adhesion method of JIS Z2801:2000 "Antibacterial processed products - Antibacterial test method, antibacterial effect". After inoculation of the virus on the surface of the test specimen, the conditions were 25°C for 24 hours, and polyethylene film was used as a control. The infectivity of the virus was determined by the plaque measurement method described in Appendix B of JIS L1922 "Antiviral test method for textile products", and the antiviral activity value was calculated using the following formula. An antiviral activity value of 2 or more was evaluated as having antiviral effect. M = Log(A / B) = Log(A) - Log(B) M: Antiviral activity value Log(A): Logarithmic value of the infectivity after 24 hours of reaction in the control group Log(B): Logarithmic value of the infectivity of the test specimen after 24 hours of reaction If the antibacterial activity value (M) is 2.0 or higher, it is determined to have an antiviral effect.
[0061] As is clear from Table 2, the coating materials of the Examples have favorable antibacterial and antiviral properties compared to the coating materials shown in the Comparative Examples, and it was confirmed that the effects persist even after wiping off with alcohol.
[0062] The antibacterial and antiviral coating composition of the present invention has excellent dispersion stability and excellent antibacterial and antiviral properties, and furthermore, the effects are sustained even after wiping with alcohol. Therefore, sheets printed with this antibacterial and antiviral coating composition can be suitably used for materials that are repeatedly cleaned, such as housing construction materials, partition boards in various public facilities and facilities visited by an unspecified number of people, curtains, etc.
[0063] [Table 1]
[0064] [Table 2]
Claims
1. The composition comprises: (a) a polymer having a polyorganosiloxane structure and a hydroxyl group; (b) a polymer not having a polyorganosiloxane structure; (c) a curing agent having a functional group capable of reacting with the hydroxyl group; (d) an antibacterial / antiviral agent; and (e) a dispersant; The coating composition, wherein the antibacterial and antiviral agent (d) is in particulate form and has an average particle size of 0.1 μm to 5.0 μm.
2. The coating composition according to claim 1, wherein the antibacterial and antiviral agent (d) comprises at least one selected from the group consisting of inorganic fine particles (d-1) containing at least one metal ion selected from the group consisting of gold, silver, copper, tin, zinc, and platinum, calcium oxide (d-2), a component extracted from Kumazasa (Japanese Sasa) (d-3), and a compound (d-4) having a cationic group in the molecule.
3. 3. The coating composition according to claim 1, wherein a content of the antibacterial and antiviral agent (d) is 0.15 to 15 mass% relative to 100 mass% of the total solid content of the polymer (a), the polymer (b), and the curing agent (c).
4. 4. The coating composition according to claim 1, wherein the dispersant (e) has a carboxyl group and / or an amino group.
5. A coated article having a coating layer formed on a plastic film or a paper substrate from the coating composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
Antiviral agent, paint and base which contain the same
JP2003221304A
Antibacterial paste
JP2004026841A
Hardenable antimicrobial dental compositions and methods
JP2008533009A
Self-repairing film
JP2014181207A